When the mountain unites. Assistance and hospitality in the Cantabrian mountains (13th-16th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
In the dense network of hospitals attested in medieval Asturias, those hospitals built on the desert and steep mountain passes form a remarkable ensemble. These hospitals and inns distinguished themselves from other welfare institutions due to their difficult location at the pass accesses, on or close to the mountain peaks. And from this location derive some basic welfare functions that are somewhat different from the services offered by urban hospitals or those located on the Asturian Way of St James: providing orientation to travellers, keeping the paths clear of snow in winter, and ensuring the supply of food. This kind of charitable assistance went beyond modest accommodation and could rely on the invaluable help of the Castilian monarchs.
Keywords: Middle Ages; Mountains; Spain; Asturias; Hospitals